Management of the landscape in the public areas of the region of Murcia, Spain - Sánchez-Sánchez, Miguel Ángel; Belmonte-Serrato, Francisco; Ballesteros-Pelegrín, Gustavo (Geographicalia, 2018)
The Region of Murcia, in the Southeast of Spain, has a great landscape diversity and the public forests contribute in an important way to that diversity. The European Landscape Convention obliges and commits to the management thereof, being developed through rules and strategies by local and regional administrations. In this work, landscape management in the public forests of the Region of Murcia is studied, according to different normative documents, both general and specific, referring to protected natural areas. The documents, international, national and regional, have been analyzed and valued, with incidence in the management of the landscape of the public forests. It was found that the largest number of measures fall on those included within the protected areas.